THE USE OF BOOKS IN CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) - Bezilova, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Connection between language and content in school environment is important, especially when we teach our students to be independent language users. The present paper investigates the connection between language and content goals. Research sample consisted of 10 and 11 years old primary school students (N = 12, M=1, F=11). The research was focused on the book Your Body, where vocabulary connected to body was being taught. New vocabulary was presented in the context, afterwards, new vocabulary and phrases were being thought through the mind maps. The case study approach was used to get an in-depth analysis of the research problem. The main aim of the research was to connect language and content, where the main emphasis was put on the content. The paper answers the research question focused on the role of the books in language and content integrated learning. The results of the research show that books are a great connection between language and content goals and can be used in content and language integrated learning.